2019
DOI: 10.1039/c9cc03032h
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared circularly polarized luminescence from chiral Yb(iii)-diketonates

Abstract: We report a rare example of near infrared circularly polarized luminescence (NIR-CPL) in the 920–1050 nm region associated with the f–f transitions of Yb diketonate complexes bearing chiral ancillary ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 26 publications
5
82
0
Order By: Relevance
“…The room temperature dissymmetry g lum factor [11b] can be determined for each CPL contribution with the values of +/−0.013 for the sharp intense band around 10235 cm −1 , −/+0.004 for the band around 9891 cm −1 and +/−0.002 for the band around 9625 cm −1 for (+) / (−) ‐ Yb , respectively. These values are in the same range as those previously reported in the literature [10] . Finally, NIR‐CPL in solid‐state was measured at room temperature under an irradiation of 360 nm (27778 cm −1 ) giving rise to three contributions (Figures 4 and S15).…”
Section: Figuresupporting
confidence: 76%
See 1 more Smart Citation
“…The room temperature dissymmetry g lum factor [11b] can be determined for each CPL contribution with the values of +/−0.013 for the sharp intense band around 10235 cm −1 , −/+0.004 for the band around 9891 cm −1 and +/−0.002 for the band around 9625 cm −1 for (+) / (−) ‐ Yb , respectively. These values are in the same range as those previously reported in the literature [10] . Finally, NIR‐CPL in solid‐state was measured at room temperature under an irradiation of 360 nm (27778 cm −1 ) giving rise to three contributions (Figures 4 and S15).…”
Section: Figuresupporting
confidence: 76%
“…Among them, the highest value of g lum =1.38 measured for the Cs[Eu((+)‐hfbc) 4 ] complex (where hfbc=3‐heptafluoro‐butylryl‐(+)‐camphorato) [7] . Another chemical approach is to associate achiral Ln(β‐diketonate) n (2≤n≤4) units to chiral ligands such as binaphtyl derivatives, [8] cyclohexane diamine, [9] or pyridinebisoxazoline [10] . In the near infrared (NIR) region i. e. from 700 to 1300 nm, Nd III and mostly Yb III ‐centered emissions are likely to be favoured, even if NIR‐CPL studies for these ions remain scarce [10,11] …”
Section: Figurementioning
confidence: 99%
“…Yb 3+ emission entirely falls in the near‐infrared (NIR) region ( 980 nm) presenting only the 2 F 5/2 2 F 7/2 transition. So far, very few examples of Yb 3+ ‐centred CPL activity have been reported, [119–121] therefore the B CPL analysis could be performed only on two complexes bearing β‐diketonates (TTA, thenoyltrifluoroacetonate) as sensitizing ligands (Table 9). [120] Given their low quantum yields (<0.01) the B CPL values are accordingly moderate (2.5 m −1 cm −1 for Yb L14 (TTA) 3 and 5.2 m −1 cm −1 for Yb L16 (TTA) 3 ), even if their g lum values are in line with the g lum values recorded for Tb 3+ and for the 5 D 0 7 F 2 Eu 3+ transition, that is, in the order of 10 −2 .…”
Section: Cpl Emittersmentioning
confidence: 99%
“…Other chiral Sm 3+ complexes have been also reported (Petoud et al, 2007 ; Kreidt et al, 2018 ; Cotter et al, 2019 ). Aside from Eu 3+ and Sm 3+ , other lanthanides ions, such as Nd 3+ , Tb 3+ , Dy 3+ , and Yb 3+ have been used in chiral complexes as optically active luminescence-polarized emitters, and they will be described in the following section (Maupin et al, 1998 , 2000 ; Dickins et al, 1999 ; Morita et al, 2000 ; Petoud et al, 2007 ; Casanovas et al, 2017 ; Leonzio et al, 2017 ; Górecki et al, 2018 ; Zinna et al, 2019 ). Concerning the MD contribution to the total transition dipole moment in a f–f transition, Richardson classified those into types DI, DII, and DIII where DI is expected to exhibit the largest dissymmetric factor (e.g., 5 F 1 in Eu 3+ ) and DII and DIII lower values, for instance, 4 H 5/2 and 5 F 5 in Sm 3+ and Tb 3+ , respectively, which are type DII transitions (Richardson, 1980 ).…”
Section: The Success Of Lanthanide Complexes Using Chiral Organic Ligmentioning
confidence: 99%
“…This points out empirically the importance of having a large amount of chiral centers around the Ln 3+ coordination environment for enhancing the dissymmetry factor. By replacing Eu 3+ with Yb 3+ , Di Bari and coworkers obtained [Yb( L5 )(tta) 3 ] and [Yb( L6 )(tta) 3 ] (tta = thenoyltrifluoroacetone), for which | g lum | values of 0.019 and 0.029 could be recorded for the 2 F 5/2 transition (Zinna et al, 2019 ), one of the rare examples of the NIR-CPL signal reported up to date.…”
Section: The Success Of Lanthanide Complexes Using Chiral Organic Ligmentioning
confidence: 99%